2020
DOI: 10.1002/cnr2.1314
|View full text |Cite
|
Sign up to set email alerts
|

Cystic adrenal lesions: A report of five cases

Abstract: Background Cystic adrenal lesions are rare and uncommon manifestation with few cases reported so far. Different types of adrenal cysts have been described with heterogeneous etiology and overlapping clinical findings, ranging from benign to malignant cystic neoplasm. They are usually asymptomatic or may rarely present with abdominal pain or fullness. Optimum management of adrenal cysts still remain controversial, owing to its low incidence. In this study, we report our institutional experience on diagnosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Several primary and metastatic tumors in the adrenal gland may develop cystic changes, thus entering in the differential diagnosis with adrenal cysts and pseudocysts. These include cystic regressive and hemorrhagic degenerative changes in adrenal cortical adenoma, adrenal cortical carcinoma, pheochromocytoma, hemangioma, lymphangioma, angiosarcoma, vascular malformations, renal cell carcinoma, mature teratomas, ectopic thyroid nodules, and even in metastases [62,63,65,67,[73][74][75]. The morphological distinction is generally straightforward in the presence of a conventional histological component of the individual neoplasms.…”
Section: Question 3: What Are the Pathological Correlates Of Adrenal ...mentioning
confidence: 99%
“…Several primary and metastatic tumors in the adrenal gland may develop cystic changes, thus entering in the differential diagnosis with adrenal cysts and pseudocysts. These include cystic regressive and hemorrhagic degenerative changes in adrenal cortical adenoma, adrenal cortical carcinoma, pheochromocytoma, hemangioma, lymphangioma, angiosarcoma, vascular malformations, renal cell carcinoma, mature teratomas, ectopic thyroid nodules, and even in metastases [62,63,65,67,[73][74][75]. The morphological distinction is generally straightforward in the presence of a conventional histological component of the individual neoplasms.…”
Section: Question 3: What Are the Pathological Correlates Of Adrenal ...mentioning
confidence: 99%
“…Functional cysts and malignant or potentially malignant cysts are usually surgically treated. Cysts over 5 cm and symptomatic cysts smaller than 5 cm are also indications for surgery [ 2 , 13 ]. Although it is more recommended to enucleate the cyst laparoscopically while preserving the adrenal gland.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Some have also reported adrenal lymphangiomas accompanied by abnormal hormonal secretions, presumably due to compression of the adrenal artery or medulla. 5 Ellis et al observed that these tumors are more frequently found in women, and more commonly seen in the right adrenal gland. 1 As it was the case for this patient, on a histological level, lymphangiomas are often seen on H&E staining as polycystic lesions lined with endothelium-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most lymphangiomas are asymptomatic, although incidences where these tumors were discovered after symptoms such as abdominal pain, palpable abdominal mass, hemorrhage, and infections have been reported 1,2 . Some have also reported adrenal lymphangiomas accompanied by abnormal hormonal secretions, presumably due to compression of the adrenal artery or medulla 5 . Ellis et al .…”
Section: Discussionmentioning
confidence: 99%